문화관광축제의 웹콘텐츠 분석에 관한 연구 - 전영철(Young-Chul Chun) (한국콘텐츠학회 논문지, 6(4), 2006)
This study was to analyze web contents of major cultural tourism festival. And suggest to contents development. Study method is contents analysis and comparative study by suggest data. According to the results, need for independent domain, provide to foreign language information, maintenance membership administration through membership e-mail service, provide to segmentation board, provide to dynamic information should be consideration to visitror's movement line. 본 연구는 문화관광부가 지정한 문화관광축제들에 대한 웹콘텐츠를 분석하고 이를 기반으로 콘텐츠구성 방안을 제시하고자 하였다. 연구방법은 웹콘텐츠를 분석하고 객관적 데이터를 바탕으로 비교평가를 실시하였다. 분석결과 독자적인 도메인 구축의 필요, 외국어 정보의 제공, 회원 제도를 통한 메일링 서비스 등 수시로 지속적인 회원관리 서비스 필요, 세분화된 게시판 제공, 방문객의 동선을 고려한 동적정보 제공 등을 제시하였다.